The cake fortified with rice bran and market available one: An evaluation of texture, colour and nutritional qualities - Bagchi, Torit Baran; K Chakraborty; A.N. Pattnaik; S. Sarkar; N. Basak; M. Sivashankari; P. Swain; S.K.Sahoo (ORYZA-An International Journal of Rice, 2024)
Rice bran is the outer pericarp of the rice endosperm. It is the underutilized milling bi-product of rice, which is generally used for cattle feeds and extraction of oil. However, the whole bran is packed with many essential bioactive molecules and fibers, which have many health benefits. In this study, the whole bran was utilized for making the cake. The textural profile analysis reveals that cakes fortified with rice bran (CRB) showed lower hardness (661.10-1429.90 g) but higher adhesiveness (-3.5 to -19.6 g-sec) and cohesiveness (72.6 to 80.6%) as compared to market available cakes (MAC). With respect to colour parameters, CRB was generally darker (L* = 33.96 to 39.25) than MAC (L* = 37.39  to 37.92) except market available chocolate cake (L*=17.34), which was darkest one. However, CRB was superior to MAC for different nutritional parameters. The minerals (Fe, Zn) content of CRB (Fe: 22.25 to 28.30 ppm and Zn: 14.68 to 16.14 ppm) was higher than MAC (Fe: 11.25 to 17.03 ppm and Zn: 6.24 to 7.61 ppm). There was higher level of phenolics content, flavonoids content(0.43 to 0.76 mg CE/g) and protein content (12.94 to 18.76%) in case of all the CRBs as compared to MACs. The total soluble sugar content was lower but antioxidant activity was higher in CRBs as compared to MACs. Therefore, CRB is one of the healthy alternatives for proper utilization of rice milling bi-product, rice bran.